Erigo Customer Loyalty at Shopee E-Commerce - Prido Risnaldi; Hartoyo; Prasetya, Prita (School of Business, IPB University (SB-IPB), 2023)
Digital marketing is using digital technology to develop channels to reach consumers more effectively. The millennial era is concerned with the consumer experience when buying, but the problems and opportunities they face are building a good consumer experience in a digital context. The aims of this study were (1) to analyze the effect of experience on Erigo's customer satisfaction, (2) to analyze the effect of satisfaction, trust and commitment on Erigo's customer loyalty, and (3) to formulate managerial implications that can increase satisfaction, trust, commitment and Erigo consumer loyalty. The participants in this study were Erigo's customers who met certain criteria using a purposive sampling technique. Five to ten samples are required for each variable parameter estimation. This study used a total sample of 347 people using SEM-PLS. Based on the research results, (1) the consumer experience variables that influence customer satisfaction are competence, helpfulness, personalization, value for time. Meanwhile, the variables of consumer experience that have little effect on customer satisfaction are accessibility, customer recognition, problem solving, and promise fulfillment, (2) Trust and commitment have an effect on consumer loyalty, but consumer satisfaction has less effect on consumer loyalty, (3) The results of the study show that the level of customer satisfaction, trust, commitment and loyalty has not been achieved optimally with the customer experience approach. Managerial implications of using the STP technique (Segmentation, Targeting, Positioning) are useful for increasing Erigo consumer satisfaction, trust, commitment and loyalty to Shopee e-commerce. Keywords: digital marketing, consumer experience, consumer satisfaction, consumer loyalty, SEM-PLS